2020
DOI: 10.1371/journal.pbio.3000926
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and lineage dynamics of a transmissible cancer in Tasmanian devils

Abstract: Devil facial tumour 1 (DFT1) is a transmissible cancer clone endangering the Tasmanian devil. The expansion of DFT1 across Tasmania has been documented, but little is known of its evolutionary history. We analysed genomes of 648 DFT1 tumours collected throughout the disease range between 2003 and 2018. DFT1 diverged early into five clades, three spreading widely and two failing to persist. One clade has replaced others at several sites, and rates of DFT1 coinfection are high. DFT1 gradually accumulates copy nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 60 publications
10
55
0
Order By: Relevance
“…We surprisingly observed a high amount of nuclear and mitochondrial polymorphism in MtrBTN2 samples. This polymorphism defines two sublineages that co-exist and spread in the same populations, as it has been observed in other transmissible cancers (CTVT: Baez-Ortega et al 2019, DFTD: Kwon et al 2020, Patton et al 2020.…”
Section: Discussionmentioning
confidence: 72%
“…We surprisingly observed a high amount of nuclear and mitochondrial polymorphism in MtrBTN2 samples. This polymorphism defines two sublineages that co-exist and spread in the same populations, as it has been observed in other transmissible cancers (CTVT: Baez-Ortega et al 2019, DFTD: Kwon et al 2020, Patton et al 2020.…”
Section: Discussionmentioning
confidence: 72%
“…Given that we analysed only 76 nucleotide positions and that the mtCOI divergence is not very strong, we believe polymorphism observed among tumors could more likely be due to structural rather than point variations, such as insertion-deletion and chromosomal losses or gains, or recombination leading to loss of heterozygosity, that are widespread in cancer (McClelland 2017, Nichols et al 2020 and have been reported in other transmissible cancers (e.g. in DFT1 and DFT2, Kwon et al 2020). According to the genotyping method used (competition of the two allele fluorescences), partial or complete chromosomal losses or gains results in a modification of the ratio of fluorescences of the two alleles of hyperploid MtrBTN2 tumors and of the ratio of tumor and host genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In Tasmanian devils two independent transmissible cancers lineages have emerged in the last 30 years. In bother cases, although at different spatiotemporal scales, genome studies have shown early diversification into sublineages and secondary co-existence of some divergent sublineages (Baez-Ortega et al 2019, Kwon et al 2020Patton et al 2020). Studies in marine bivalves also showed multiple emergences (two in Cerastoderma edule, Metzger et al 2016 and two in Mytilus trossulus, Yonemitsu et al 2019) and for the first time in transmissible cancer research, transmissions crossing the species barrier (BTN lineage in Polititapes aureus has a Venerupis corrugata origin, Metzger et al 2016, and MtrBTN2 in M. edulis and M. chilensis has a M. trossulus origin, Yonemitsu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A major difference between non-communicable cancers and transmissible cancers is that classical cancer cells have to ‘reinvent the wheel’ at every step – from initiation and progression to metastasis, but ultimately, they all die with the death of the host. In contrast, in transmissible cancers, clonal cell lineages are passed from host to host, and thus evolve as novel parasitic life forms, as seen in CTVT and DFTD, where these cancer lineages have continued to evolve since their initial emergence ( Pearse et al, 2012 ; Dujon et al, 2020a ; Kwon et al, 2020 ). Thus, investigating whether the tumoral GPC has been adjusted by selection in a way that optimizes the parasitic lifestyle will also provide insight into the evolution of parasitism.…”
Section: Group Phenotypic Composition In the Context Of Cancermentioning
confidence: 99%